Pemediasian Kinerja Keuangan: Manajemen laba dan Kebijakan dividen terhadap Nilai Perusahaan - Molina Molina; Aditya Aliendia (LPMP Imperium, 2024)
This research was conducted with the aim of analyzing the effect of earnings management and dividend policy on firm value with financial performance as the intervening variable. Firm value is an indicator of financial performance for companies that have gone public. High corporate value will indicate high shareholder prosperity. The research was conducted using population data from 168 listed manufacturing companies listed on the Indonesia Stock Exchange for the period 2013 - 2019. The sampling method in this study used purposive sampling and used the SEM PLS regression analysis technique and path analysis which was processed using the WarpPLS 7.0 program. The research results show that earnings management and dividend policy directly affect financial performance and firm value. While financial performance is able to mediate the relationship between earnings management and firm value, as well as the relationship between dividend policy and firm value, financial performance can mediate these two variables.